An investigation of fermentation and maturation temperatures on the chemical and sensory characteristics of the starter-culture based marula fruit wines - Ramoba, Louis (My University, 2024)
Temperature is an important factor that affects the growth and activities of wine microorganisms, which then influences the chemical profile and consequently the organoleptic characteristics of the wine. The aim of the study was to evaluate the influence of varying temperatures for fermentation, maturation and storage conditions on the chemical, nutritional and sensory characteristics of starter-culture-based marula fruit wines. Clarified sweetened marula fruit juices were fermented at 15 °C and 25 °C, and one portion from each was matured and aged at the same temperatures. Another portion from each fermented wine was matured and aged at 4 °C, whereas the reference wine was fermented at 25 °C using the clarified unsweetened marula fruit juice, and matured and stored at 15 °C and 4 °C. The microorganisms isolated from bottled aging wines were identified with the 16S rRNA region. Organic chemicals such as sugars, alcohols, glycerol, pH, acids, esters, tannins, and antioxidants were determined using conventional chemical analysis method, spectroscopy and chromatographic methods. Selected nutrients such as minerals, proteins, cholesterol, crude fats and vitamin C were determined as well. All the wines were subjected to panel testing. The microbial species that were identified in the aging marula wines at different temperatures include Saccharomyces cerevisiae, Lactobacillus brevis, Acetobacter lovaniensis, Acetobacter ghanensis, Raoultella terrigena, Raoutella ornithinolytica and Bacillus species. The naturally occurring citric acid which influences titratable and total acidity in wines was detected at higher concentration, while lactic and acetic acids were the least produced. An increase in higher alcohols and spicy esters was observed in the wines that were produced at 25 °C, whereas the level of fruity esters increased in wines that were stored at 4 °C. The wines preserved and improved some of the essential nutrients such as proteins and minerals, whereas vitamin C levels dropped in the wines that were produced at elevated temperatures. The wine that was fermented at 15 °C, matured and stored at 4 °C was the most appreciated as compared to wines that were produced at elevated temperatures. These findings asserted the development of good flavours in wines produced at lower temperatures, as is the case with marula fruit wine wherein the complex intensive flavour profile and good balance can be attained at lower production temperatures.
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2024
Keywords: Temperature; Wine; Chemicals; Species; Fermentation; Fruit wines; Wine and wine making; Sclerocarya birrea